Mucosal antibodies in inflammatory bowel disease are directed against intestinal bacteria. Issue 3 (March 1996) - Macpherson, A; Khoo, U Y; Forgacs, I; Philpott-Howard, J; Bjarnason, I
Abstract : In contrast with normal subjects where IgA is the main immunoglobulin in the intestine, patients with active inflammatory bowel disease (IBD) produce high concentrations of IgG from intestinal lymphocytes, but the antigens at which these antibodies are directed are unknown. To investigate the specificities of these antibodies mucosal immunoglobulins were isolated from washings taken at endoscopy from 21 control patients with irritable bowel syndrome, 10 control patients with intestinal inflammation due to infection or ischaemia, and 51 patients with IBD: 24 Crohn's disease (CD, 15 active, nine quiescent), 27 ulcerative colitis (UC, 20 active, seven inactive). Total mucosal IgG was much higher (p < 0.001) in active UC (median 512 micrograms/ml) and active CD (256 micrograms/ml) than in irritable bowel syndrome controls (1.43 micrograms/ml), but not significantly different from controls with non-IBD intestinal inflammation (224 micrograms/ml). Mucosal IgG bound to proteins of a range of non-pathogenic commensal faecal bacteria in active CD; this was higher than in UC (p < 0.01); and both were significantly greater than controls with non-IBD intestinal inflammation (CD p < 0.001, UC p < 0.01) or IBS (p < 0.001 CD and UC). This mucosal IgG binding was shown on western blots and by enzyme linked immunosorbent assay (ELISA) to be principally directed against the bacterial cytoplasmic rather than the membrane proteins. Total mucosal IgA concentrations did not differ between IBD and controls, but the IgA titres against faecal bacteria were lower in UC than controls (p < 0.01). These experiments show that there is an exaggerated mucosal immune response particularly in active CD but also in UC directed against cytoplasmic proteins of bacteria within the intestinal lumen; this implies that in relapse of IBD there is a breakdown of tolerance to the normal commensal flora of the gut.